Serbia and Montenegro : Poverty Reduction Strategy Paper-Progress Reports. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper discusses the First Progress Report on the implementation of the Poverty Reduction Strategy (PRS) in Serbia. The Poverty Reduction Strategy Paper (PRSP) for Serbia and its implementation complement the efforts of Serbia in the European Union integration process. The PRSP also includes a focus on the need to reform the public administration with the goal of increasing the efficiency and transparency of policy coordination and governance in implementing the programmatic documents of the Republic of Serbia as well as in improving the way of governing the overall and public sector policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet